Analisis pengaruh pertumbuhan penduduk, pendidikan, pertumbuhan ekonomi, pengeluaran pemerintah, tingkat pengangguran dan inflasi terhadap tingkat kemiskinan di Kota Jambi - Dira Puji Lestari; Junaidi Junaidi; Siti Aminah (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
This research entitled “Analyzing the affect of population growth, education, economic growth, government expenditure, unemployment rate and inflation towards the poverty rate of Jambi city”. The purpose of this research were to analyze the population growth, education, economic growth, government expenditure, unemployment rate, inflation and the poverty rate and to analyze the affect of population growth, education, economic growth, government expenditure, unemployment rate, and inflation towards the poverty rate of Jambi city.This research used ordinary least squares. The F test indicated that simultaneously the variables of the population growth, education, economic growth, government expenditure, unemployment rate, and inflation significantly affected the poverty rate of Jambi city. While t test revealed that partially education, government expenditure, unemployment rate and inflation affected the poverty rate of Jambi city. Meanwhile, the variables of population growth and economic growth insignificant to the poverty rate of Jambi city.